TINJAUAN YURIDIS TENTANG RESIKO PERJANJIAN PENDAHULUAN DALAM PELAKSANAAN JUAL BELI RUMAH PADA PENGEMBANG PERUMAHAN PT. RUMAH RAKYAT DI SAMARINDA - Yuliansyah Yuliansyah (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACT Along with the increase of population, the need will be increasing as well. In order fulfillment and improvement of people's welfare, development plays an important role. The development contains major changes, which include changes in the economic structure, change the physical territory, changing consumption patterns, changes in natural resources and the environment, and so on.Housing and housing is a basic human need and has a very strategic role in the formation of character and personality of the nation, and needs to be nurtured and developed for the continuation and improvement of the lives and livelihood of the people. Housing and settlement can not be seen as a means of life needs solely, but more than that a man in the process of creating space live life to promote himself, and reveal identity. To ensure legal certainty and order in the home construction can only be done on land owned by the rights over the land in accordance with the legislation in force.